Queer Carnival : festivals and Mardi Gras in the South - Stone, Amy L. (New York University Press, 2022)
"As LGBTQ people gain more legal rights, it's important to think of more complex ways of being included in society. From the Mardi Gras celebrations in the Deep South to the Mummers Parade in Philadelphia to the Portland Rose Festival, communities across the United States gather together to celebrate, participate in parades, encourage tourism, cultivate local traditions, and craft a sense of place. I am interested in large public festivals like Fiesta San Antonio that are intended to include everyone in the city, because these festivals are supposed to be a time when the city comes together as one to appreciate the diverse contributions of people within the city. During festivals, whose culture gets included and valued, which events are allowed, and how different communities are represented, become socially significant and fraught questions. Festival participation can be a rich site for LGBTQ participants to be valued for their cultural differences and find a sense of belonging in the city"--